Learning Strategies of Islamic Education Teachers for Deaf Students at SLB ABC Melati Aisyiyah Tembung - Amanda, Della Latifah; Nasution, Wahyudin Nur (FKIP - Universitas Riau, 2025)
This study aims to identify the learning strategies used by Islamic Education (PAI) teachers for deaf students at SLB ABC Melati Aisyiyah Tembung, as well as to determine the supporting and inhibiting factors in the use of these strategies. The research method used is qualitative, specifically a type of field research. This study falls under descriptive qualitative research, with data obtained in the form of words, descriptions, and behaviors presented in a report format. Data collection techniques include observation, interviews, and documentation studies. The data analysis techniques used in this study are data reduction, data presentation, and data verification. The data validity technique employed is triangulation, which includes source triangulation, time triangulation, and technique triangulation.The results of the study indicate that the learning strategy used by Islamic Education teachers for deaf students at SLB ABC Melati Aisyiyah Tembung is active learning, in which deaf students are more actively involved in the classroom. A student-centered approach is applied, meaning the learning process focuses on the students, while still under the supervision and guidance of the teacher, using demonstration or practical methods and oral methods. Supporting factors in the implementation of Islamic Education learning strategies in deaf classes include adequate classroom facilities, parental involvement, and additional religious programs provided by the school. Meanwhile, inhibiting factors include limited learning resources and communication barriers.